Analisis Penerapan Disiplin Kerja Pada Pengadilan Negeri Bogor - Silvia Harviana; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine how the implementation of work discipline at the Bogor District Court, how the attendance system to support employee discipline and how the Bogor District Court strategy in maintaining work discipline. This research method is a qualitative descriptive approach. This research was conducted at the Bogor City District Court. Data collection techniques are obtained from primary data derived from observation, interviews and documentation while secondary data through literature sources. The data that has been collected is analyzed with the stages of data collection, data reduction, data presentation and, conclusions. The results showed that 1. SIKEP / IKA digital attendance which is carried out online as a form of implementing work discipline makes Bogor District Court employees more diligent to come to the office on time and return from the office after office hours. 2. SIKEP / IKA is a real time attendance system where Bogor District Court employees must download the SIKEP / IKA application on each employee's cellphone and must be filled in the office area because the attendance system can only receive absences when the employee's location is in the Bogor District Court area. 3. SIKEP / IKA is a strategy of the Bogor District Court in maintaining the work discipline of Bogor District Court employees. If there are employees who forget to fill in the SIKEP / IKA or are late filling in the SIKEP / IKA application. The risk of such actions is the deduction of remuneration and the obligation to make an official report. The recommendation that we provide from this research is that the Bogor District Court must provide an adequate internet connection to prevent server interruptions on employees' cellphones so that there are duplicate connections from the Bogor District Court office wifi.